PROTECTION OF HUMAN PERSONALITY THROUGH CRIMINAL PROCEDURAL MEANS - Buneci, Bogdan (International Journal of Legal and Social Order, 2024)
The protection of human personality in criminal proceedings is a fundamental pillar of the justice system, based on a series of essential principles and procedural means. In this regard, the fundamental principles leading to the protection of human personality are presented, such as the benefit of the doubt, the right to a fair trial within a reasonable time, respect for human dignity and privacy, the right to defense and freedom, but also the right to an interpreter for persons who do not understand the official language. Procedural means such as legal aid, the exclusion of illegally obtained evidence, the protection of witnesses and victims, as well as the regulation of preventive measures are also analyzed, all of which contribute to ensuring respect for fundamental rights and freedoms. Respect for these norms and guarantees is essential to prevent abuses and to maintain the fairness and integrity of the judicial system.